2017
DOI: 10.1007/s00253-017-8473-4
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria isolated from yak milk show probiotic potential

Abstract: Probiotic industries strive for new, efficient and promising probiotic strains that impart a positive impact on consumer health. Challenges are persisting in isolation, screening, and selection of the new indigenous probiotic strains. In the present research, we explored the probiotic potential of 17 lactic acid bacteria isolated from Yak milk in a series of in vitro tests. We also demonstrated their health benefits, i.e., cholesterol degradation, lactose digestion, antimicrobial activity, antioxidant, and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 73 publications
5
22
0
1
Order By: Relevance
“…Li et al [50] reported that the DPPH free radical scavenging rate by the intact cell of the L. plantarum C88 strain was 53.05% at the dose10 10 UFC/ml. In a study analogous to us, Kaur et al [51] documented about more than 50% of this scavenging capacity of theYbis, L5 and Yb LAB strain with their ICs. Furthermore, our results showed that ICs exhibited higher DPPH radical scavenging rate than that of CFSs.…”
Section: Discussionsupporting
confidence: 53%
“…Li et al [50] reported that the DPPH free radical scavenging rate by the intact cell of the L. plantarum C88 strain was 53.05% at the dose10 10 UFC/ml. In a study analogous to us, Kaur et al [51] documented about more than 50% of this scavenging capacity of theYbis, L5 and Yb LAB strain with their ICs. Furthermore, our results showed that ICs exhibited higher DPPH radical scavenging rate than that of CFSs.…”
Section: Discussionsupporting
confidence: 53%
“…The intimate contact between probiotics and pathogenic bacteria occurs during co-aggregation and the antimicrobial substances produced by the former can inhibit pathogens (61). In addition, the reports of the antiviral and anticancer activities are good examples of much broader than originally considered health-promoting activities attributed to probiotic LAB (62,63). Although the antiviral and anticancer abilities of the isolated LAB were not characterized in this study, it would be an interesting topic for further studies.…”
Section: Discussionmentioning
confidence: 89%
“…The microflora in raw camel milk consists of Streptococcus, Lactococcus, Weissella, Pediococcus, Lactobacillus, and Enterococcus (Fguiri et al, 2016;Fugl et al, 2017). However, yak milk contains Lactobacillus species, Enterococcus species, Lactococcus species, Leuconostoc species, and Weissella cibaria (Kaur et al, 2017), whereas Lactococcus, Lactobacillus, Leuconostoc, Streptococcus, Enterococcus, Macrococcus, Weissella, and Bacteroidetes were the dominant flora in raw milk (Gao et al, 2017). Furthermore, LABs function as a starter culture in raw animal milk and contribute to the fermentation of cheese, kefir, and yogurt.…”
Section: Introductionmentioning
confidence: 99%